Mammographic screening in BRCA1 mutation carriers postponed until age 40: Evaluation of benefits, costs and radiation risks using models. (August 2016) - Obdeijn, Inge-Marie; Heijnsdijk, Eveline A.M.; Hunink, M.G. Myriam; Tilanus-Linthorst, Madeleine M.A.; de Koning, Harry J.
Abstract: Purpose: BRCA1 mutation carriers are offered screening with magnetic resonance imaging (MRI) and mammography. The aim of this study was to weigh benefits and risks of postponing mammographic screening until age 40. Methods: With the MISCAN microsimulation model two screening protocols were evaluated: 1) the current Dutch guidelines: annual MRI from age 25–60, annual mammography from age 30–60, and biennial mammography in the nationwide program from age 60–74, and 2) the modified protocol: with annual mammography postponed until age 40. A cost-effectiveness analysis was performed. The risks of radiation-induced breast cancer mortality were estimated with absolute and relative exposure-risk models of the 7th Biological Effects of Ionising Radiation Committee. Results: Current screening guidelines prevent 13, 139 breast cancer deaths per 100, 000 BRCA1 mutation carriers. Postponing mammography until age 40 would increase breast cancer deaths by 23 (0.17%), but would also reduce radiation-induced breast cancer deaths by 15 or 105 using the absolute and relative risk model respectively per 100, 000 women screened. The estimated net effect is an increase of eight or a reduction of 82 breast cancer deaths per 100, 000 women screened (depending on the risk model used). The incremental cost of mammograms between age 30–39 is €272, 900 per life year gained. Conclusions: The modified protocol may be slightly less effective or even better than the current guidelines. The high cost-savings justify a possible small loss of effectiveness. Highlights: The net benefit of mammographic screening from age 30–39 years is very small or even negative. The incremental cost of mammograms between age 30–39 is €272, 900 per life year gained. Postponing mammography until age 40 would reduce radiation-induced breast cancer deaths by 50%.